Analysis of prismatic lithium‐ion battery degradation based on an electrochemical‐thermal‐degradation model. (3rd September 2022) - Zhang, Hongya; Li, Chengshuai; Chen, Hao; Fang, Haisheng
Summary: Understanding the performance degradation of lithium‐ion batteries will be conducive to improving the endurance of electric vehicles. A one‐dimensional electrochemical model (1D‐EM), a three‐dimensional thermal model (3D‐TM) and an accurate degradation model are here coupled for a prismatic LFP/C battery for the first time. The degradation mechanisms include the formation of the solid electrolyte interface (SEI), Li plating (LP), and the loss of active material (LAM) of the negative electrode and positive electrode. This electrochemical‐thermal‐degradation model can accurately predict battery degradation over a wide range of temperatures ( T amb ) and current rates. The charge‐discharge process is repeated up to 1000 times, and the changes in the charge‐discharge curve reflect the battery degradation to some extent. Capacity loss varies from −10°C to 50°C, which can be divided into three stages. The first stage corresponds to low T amb and is dominated by the LP, the second stage corresponds to an intermediate T amb and is dominated by the LAM and SEI formation, and the third stage corresponds to high T amb and is dominated by the LAM. Through the coupled model of 1D‐EM, 3D‐TM, and degradation model, the degradation mechanism of prismatic LFP/C battery under different working conditions is summarized, and its causes are analyzed. The results in this study show an important reference value for the degradation analysis of prismatic LFP/C battery under different operating conditions and provide a new direction for the optimization and design of prismatic LIBs degradation. Abstract : Capacity loss varies from −10 °C to 50 °C, which can be divided into three stages. The first stage corresponds to low T amb and is dominated by the LP, the second stage corresponds to an intermediate T amb and is dominated by the LAM and SEI formation, and the third stage corresponds to high T amb and is dominated by the LAM. The results show an important reference value for the degradation analysis and provide a direction for the degradation optimization.